Volcanic crystals as time capsules of eruption history - Teresa Ubide (Nature Portfolio, 2018)
Crystals can record the timing of volcanic eruptive triggers at depth by examining their zoning histories. Here, the authors analyse clinopyroxene crystal zoning from eruptions at Mount Etna, Italy from 1974-2014 and show that the intrusion of magma can trigger an eruption within 2 weeks of arrival.